2016
DOI: 10.1136/bmjopen-2016-011571
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of health-related behaviours among adolescents: a cross-sectional study based on the National Survey of School Health Brazil 2012

Abstract: Objectives: The aim of this study was to analyse the clustering of multiple health-related behaviours among adolescents and describe which sociodemographic characteristics are associated with these patterns.Design: Cross-sectional study. Setting: Brazilian schools assessed by the National Survey of School Health (PeNSE, 2012).Participants: 104 109 Brazilian ninth-grade students from public and private schools (response rate=82.7%). Methods: Exploratory and confirmatory factoranalyses were performed to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 32 publications
4
46
0
1
Order By: Relevance
“…[11][12][13] Most of the studies used self-reported questionnaires, but less than half the studies reported information about instrument validity. 9,14,17,18,[30][31][32][33]36,42,[52][53][54][59][60][61][62]65,[67][68][69][70][73][74][75][77][78][79][80][81]86,93,94,97,[99][100][101][102][103][104][105][106] Only three studies assessed sedentary behavior using accelerometers. 11,15,16 The cut-off point used in the studies varied considerably from 2 to 4 hours, although most studies used cut-off point of 2 hours of screen time: 20 studies 18,20,21,27,[30][31][32][33]…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13] Most of the studies used self-reported questionnaires, but less than half the studies reported information about instrument validity. 9,14,17,18,[30][31][32][33]36,42,[52][53][54][59][60][61][62]65,[67][68][69][70][73][74][75][77][78][79][80][81]86,93,94,97,[99][100][101][102][103][104][105][106] Only three studies assessed sedentary behavior using accelerometers. 11,15,16 The cut-off point used in the studies varied considerably from 2 to 4 hours, although most studies used cut-off point of 2 hours of screen time: 20 studies 18,20,21,27,[30][31][32][33]…”
Section: Resultsmentioning
confidence: 99%
“…In particular, clinicians at these institutions should receive more extensive training in syphilis prevention knowledge and PISTC services. At the same time, we should improve patient education so that patients feel comfortable seeking help from healthcare providers after unsafe sex [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The athletes reported on their weekly frequency of physical exercise (1,2,3,4, and ≥ 5 days per week), annual competition frequency (1 per year, or ≥ 2 per year), sports type (volleyball, basketball, handball, or soccer), and time spent practicing this sport (months). We used a validated and reproducible questionnaire from The Brazilian National School-Based Health Survey (PeNSE) (16,20) to assess the eating pattern. Food consumption was assessed based on the frequency of consumption of the 5 following healthy food items in the previous 7 days: bean, raw salad (cucumber, lettuce, tomato, carrot, and onion), vegetables (cabbage, chayote, broccoli, spinach, and pumpkin), fruits, and milk; as well as the 5 following unhealthy food items in the previous 7 days: deep-fried salty snacks, processed meat (hamburger, sausage, and ham), bagged salty snacks, sweets, and soft drinks.…”
Section: Data Collection Proceduresmentioning
confidence: 99%